A result on chromatic uniqueness of edge-gluing of graphs - Chia G.L.; Ho C.-K. (2023)
In this paper, it is shown that the graph obtained by overlapping the cycle Cm (m ? 3) and the complete bipartite graph K3,3 at an edge is uniquely determined by its chromatic polynomial.